The Socially Involved Renunciate: Guru Nanak’s Discourse to the Nath Yogis, by Kamala Elizabeth Nayar and Jaswinder Singh Sandhu - Johnson, Will (Religions of South Asia, 2008)
The Socially Involved Renunciate: Guru Nanak’s Discourse to the Nath Yogis, by Kamala Elizabeth Nayar and Jaswinder Singh Sandhu. Albany, NY: State University of New York Press, 2007. xvi + 181 pp., $60 (hb), $18.95 (pb). ISBN-13 978-0-7914-7213-2 (hb), ISBN-13 978-0-7914-7214-9 (pb; June 2008).